When Accountability Becomes Ritual: Explaining The Ontological Gap In Indonesian Local Government Reporting - Soffan Marsus; Fernandes Simangunsong; Dadang Suwanda; Mulyadi Mulyadi (Universitas Sultan Ageng Tirtayasa, 2026)
This study analyzes the implementation hurdles of regional performance reporting in Tangerang Selatan City by examining the emergence of an ontological gap between formal accountability documents and operational realities. A qualitative case study approach was employed using a Relational Qualitative Database in Microsoft Access to analyze narratives from 35 informants representing policy makers, policy implementers, evaluative stakeholders, and service users. The analysis was guided by Hamdi’s policy implementation theory, focusing on the dimensions of Productivity, Linearity, and Efficiency. The findings reveal that the regional reporting ecosystem is characterized by structural fragmentation, administrative fatigue, and a temporal paradox in which reporting deadlines precede the finalization of national datasets. These conditions encourage the practice of cocoklogi (retrospective data matching) and generate “Quantum Loops,” where performance indicators exhibit artificial leaps to satisfy compliance requirements. Consequently, an ontological gap emerges between the administrative reality represented in performance reports and the substantive reality experienced by citizens and practitioners. The study concludes that accountability functions more as a ritual of compliance than as a mechanism for organizational learning and recommends the establishment of a single source of truth to improve data integration and accountability quality.